Security in the balance: How Britain tried to keep its Iraq War secrets. (February 2020) - Thomas, Owen David
State secrecy is incompatible with the values of liberal democracy if there is no publicly reasonable justification for the concealment. So how can a liberal democracy continue to keep state secrets amidst suspicion that no such justification exists or that, worse, those secrets contain evidence of wrongdoing? This article maps and critiques the justificatory strategies that were used by the British state to refuse to disclose secret material related to the 2003 Iraq War, despite widespread accusations of hidden deception and illegality. Through an analysis of the legal discourse that underpins freedom of information (FOI) and disclosure protocols, the article shows how the law regulates disclosure through a metaphorical 'balance' of public interests. This balance, however, is no balance at all. It is profoundly one-sided because security only features on one side. The law explicitly recognizes that disclosure can create insecurity for public interests, but lacks any recognition of the opposite: the insecurity of secrecy. Rather than security trumping liberal values, this law allows enduring secrecy to be framed, paradoxically, as a means to secure liberal democratic accountability. The significance of this claim is far-reaching as FOI laws in many other countries employ a similar harm-based, one-sided justificatory strategy.